The Double Trouble: Caudal Duplication Syndrome-A rare case series with review of literature - Dr Debarpita Datta; Dr Sudipta Saha; Dr Debashis Dakshit; Maity, Arup; Dr Ruchi Bansal; Dr Nupur Basu (International Journal of Medical Research and Review, 2024)
Caudal duplication syndrome (CDS) is a very rare disease entity. It includes a broad range of abnormalities and clinical symptoms, from single or partial duplication of the gastrointestinal, genitourinary and distal neural tube system organs to total duplication. There have been several ideas proposed to explain the complicated yet symmetrical abnormalities and the wide range of clinical manifestations of caudal duplication syndrome. In this case series we present two confirmed cases of Caudal Duplication Syndrome in our institute. The management for this syndrome is individualized and may include surgical intervention to fuse or excise the duplicated organs.